Türkiye’de Coğrafya Eğitimi Alanında Yapılan Lisansüstü Tezlerin (2006-2017) Eğilimleri / The Trends of Postgraduate Theses (2006-2017) on Geography Education in Turkey - Çifçi, Taner (Journal of History Culture and Art Research, 2017)
Abstract The main aim of this study is to identify theses from 2006 to today (2017) on Geography education in Turkey, classify them in terms of their genre, content, research design (model), data collection method, sample and data analysis method and define primarily preferred study subjects for Geography education in Turkey. This is a significant study as the analysis of recent postgraduate theses on Geography education with regard to different criteria will help researchers, educationalists, teachers and students. 146 master thesis and 41 doctorate theses from 2006-2017 in the electronic database of Turkish Council of Higher Education were examined with the use of Geography Education Publication Classification Form and analyzed with the use of content analysis method used in qualitative studies. According to the findings of the study, most of the postgraduate theses on Geography education in Turkey were conducted in Gazi University, Marmara University and Atatürk University. It is seen that most of the theses were conducted in 2010; however, the number of doctorate theses have been clearly decreasing. The most common study subject of both master and doctorate theses is about approach-strategy-method-technique-practice and it is emphasized that there must be more studies about different subjects. It was seen that the most preferred research design is quantitative method and it is suggested that mixed type would be used for more comprehensive studies. It is determined that mostly quantitative methods were preferred in the investigated theses and it is suggested that mixed method designs should be used for more comprehensive research studies. Both MA and doctorate theses commonly researched secondary school students and the number of participants ranged between 31 and 100. Moreover, according to the findings of the study, it is determined that mostly preferred data collection tools of the studies were questionnaires and surveys, and common data analysis methods were descriptive analysis. It is suggested that statistical analysis methods should be used more frequently. Öz Bu çalışmadaki temel amaç; 2006 yılından günümüze kadar (2017) geçen süreçte Türkiye’de coğrafya eğitimi alanında yapılan tez çalışmalarını tespit edip; tezleri türlerine, konu alanlarına, araştırma desenine (modeline), veri toplama yöntemlerine, örneklem ve veri analiz yöntemlerine göre ana hatlarıyla sınıflandırarak Türkiye’deki coğrafya eğitimi açısından öncelikli tercih edilen araştırma eğilimlerini belirlemektir. Çalışma, coğrafya eğitimi üzerine son yıllarda yapılan lisansüstü tezlerin farklı kıstaslara göre değerlendirilmesini konu edindiğinden araştırmacılara, eğitimcilere, öğretmen ve öğrencilere ışık tutacağı düşünüldüğü için önem arz etmektedir. Çalışmada 2006-2017 yıllarında yazılmış YÖK Ulusal Tez Veri Tabanında yer alan 146 yüksek lisans ve 41 doktora tezi incelenmiştir. Araştırma kapsamında elde edilen tezler “Coğrafya Eğitimi Yayın Sınıflama Formu” kullanılarak ele alınmış ve nitel araştırmalarda kullanılan içerik analizi yönteminden yararlanılarak değerlendirilmiştir. Çalışmanın bulgularına göre, Türkiye’de coğrafya eğitimi alanında yapılan lisansüstü tezlerin önemli oranda Gazi, Marmara ve Atatürk üniversitelerinde yazılmıştır. En fazla tez çalışmasının 2010 yılında yapıldığı fakat son yıllarda özellikle doktora tezleri sayısında belirgin düşüş olduğu görülmüştür. Hem yüksek lisans hem de doktora tezlerinde sıklıkla çalışılan konuların başında yaklaşım-strateji-yöntem-teknik-uygulamanın geldiği ve farklı konulara da ağırlık veren çalışmaların gerekliliği vurgulanmıştır. İncelenen tezlerde en çok nicel araştırma yöntemlerinin tercih edildiği saptanmış ve daha kapsamlı araştırmalar için karma yöntem desenlerinden yararlanılması önerilmiştir. Hem yüksek lisans hem de doktora tezlerinde yaygın olarak ortaöğretim öğrencileri ve 31-100 arası kişi ile çalışıldığı belirlenmiştir. Ayrıca çalışmanın bulgularına göre en fazla tercih edilen veri toplama araçlarının anket ve ölçek, veri analiz tekniğinin ise betimsel analiz olduğu saptanmış ve istatistiksel analiz tekniklerine ağırlık verilmesi önerilmiştir.